Expression of microRNAs is essential for arterial myogenic tone and pressure-induced activation of the PI3-kinase/Akt pathway. (13th November 2013) - Bhattachariya, Anirban; Dahan, Diana; Turczyńska, Karolina M.; Swärd, Karl; Hellstrand, Per; Albinsson, Sebastian
Abstract: Aims: The myogenic response is the intrinsic ability of small arteries to constrict in response to increased intraluminal pressure. Although microRNAs have been shown to play a role in vascular smooth muscle function, their importance in the regulation of the myogenic response is not known. In this study, we investigate the role of microRNAs in the regulation of myogenic tone by using smooth muscle-specific and tamoxifen-inducible deletion of the endonuclease Dicer in mice. Methods and results: In order to avoid effects of Dicer deletion on smooth muscle differentiation and growth, we used an early time point (5 weeks) after the tamoxifen-induction of Dicer knockout (KO). At this time point, we found that myogenic tone was completely absent in the mesenteric arteries of Dicer KO mice. This was associated with a reduced pressure-induced Akt-phosphorylation, possibly via increased phosphatase and tensin homologue (PTEN) expression, which was found to be a target of miR-26a. Furthermore, loss of myogenic tone was associated with a decreased depolarization-induced calcium influx, and was restored by the L-type channel agonist Bay K 8644 or by transient stimulation with angiotensin II (Ang II). The effect of Ang II was dependent on AT1 -receptors and activation of the PI3-kinase/Akt pathway. Conclusion: In this study we have identified novel mechanisms that regulate myogenic tone in resistance arteries, which involves microRNA-dependent control of PI3-kinase/Akt signalling and L-type calcium influx. Furthermore, we have demonstrated that transient stimulation by Ang II can have long-lasting effects by potentiating myogenic tone.